Lung volume reduction surgery since the National Emphysema Treatment Trial: Study of Society of Thoracic Surgeons Database - Decker, Marquita R.; Leverson, Glen E.; Jaoude, Wassim Abi; Maloney, James D. (The Journal of thoracic and cardiovascular surgery, 2014)
The National Emphysema Treatment Trial demonstrated that lung volume reduction surgery is an effective treatment for emphysema in select patients. With chronic lower respiratory disease being the third leading cause of death in the United States, this study sought to assess practice patterns and outcomes for lung volume reduction surgery on a national level since the National Emphysema Treatment Trial. Aggregate statistics on lung volume reduction surgery reported in the Society of Thoracic Surgeons Database from January 2003 to June 2011 were analyzed to assess procedure volume, preoperative and operative characteristics, and outcomes. Comparisons with published data from the National Emphysema Treatment Trial were made using chi-square and 2-sided t tests. In 8.5 years, 538 patients underwent lung volume reduction surgery, with 20 to 118 cases reported in the Society of Thoracic Surgeons Database per year. When compared with subjects in the National Emphysema Treatment Trial, subjects in the Society of Thoracic Surgeons Database were younger (P < .001), a larger proportion underwent the procedure thoracoscopically (P < .001), and forced expiratory volume in 1 second was 31% versus 28% of predicted (P < .001). When mortality was compared between subjects in the Society of Thoracic Surgeons Database and all subjects in the National Emphysema Treatment Trial randomized to surgery, there were no significant differences. However, mortality was 3% higher in subjects in the Society of Thoracic Surgeons Database when compared with the non–high-risk National Emphysema Treatment Trial subset (P = .005). This study demonstrates the importance of patient selection and the need to develop consensus on appropriate benchmarks for mortality rates after lung volume reduction surgery. It underscores the need for dedicated centers to increasingly address the heavy burden of chronic lower respiratory disease in the United States in a multidisciplinary fashion, particularly for preoperative evaluation and postoperative management of emphysema.